تاثير مساحيق اوراق بعض النباتات في الاداء الحياتي لخنفساء الدقيق الصدئية الحمراء - M. AL-FARHANI, IMAN; M. KHlif., JINAN (University of Thi-Qar Journal of Science, 2009)
The study deals with the effect of leaves powders of Nicotiana tabacum ,Nerium oleander ,Zizphusspina-christi , Vitex agnus-castus, Lantana camara , Myrtus communis , Clerodendroninerum and Eucalptus globules on the mortality reduction in F1progeny and repellency of leavespowders on the red flour beetle . This results showed that when we mixed the leaves powderswith crushed wheat grains in amounts of 4, 2,1, and 0.5 % weight by weight , the mortalitiesincreased with increasing mount .The leaves powders of N. tabacum ,Z. christi and C. ineriumwas the best effected the mortality of the adults after 7 days it 97.5 ,71.77 , 68.33% respectively .The losses of percentage rate in the weight grains was revesaly proprotioed with mount of powderwas the best mount 4 % reduced in the weight and also mixed leaves powder with0.92 % grainsthrough 30 days reached food reducing F1 progeny , the best effected was L .camara it reached95.12 % and producted rate reached 1.46% . The results showed that leaves powder of Mcommunis was the best effected of response index reached - 0.1at all amounts 4 % and 2 % after24 hours . The result showed was not effected the plants powdered of leaves in the percentag ofgermination of wheat grains treatment .